Analisis Faktor-Faktor Penghambat Produktivitas Publikasi Karya Ilmiah Mahasiswa PPs UNY pada Jurnal Internasional Terindeks - Pardjono Pardjono; Nuchron Nuchron; Surono Surono; Sulaeman Deni Ramdani (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
This research aims to reveal the inhibiting factors affecting the productivity of scientific papers publication of UNY graduate school students on indexed international journals, and students' expectation for the school administration to increase that productivity. This is a survey research carried out by the Graduate School of Universitas Negeri Yogyakarta (PPs UNY), involving 74 respondents. Data were obtained by means of questionnaire and were analyzed using descriptive statistical analysis. The results can be stated as follows. 1) The inhibiting factors came from external factors, namely busy workload, the high cost of international publishing, limited resource and access to printed journals subscription, and limited resource of online journals subscription. 2)  Students' expectation to increase the productivity of indexed international journals publication are improvement in the dissemination of the program, access to information and services, English writing course, free translation, establish cooperation and networking, and subscription of online and printed journals.Penelitian ini bertujuan untuk mengungkap: 1) faktor penghambat produktivitas mahasiswa dalam publikasi karya ilmiah pada jurnal internasional terindeks, 2) harapan mahasiswa kepada pengelola kampus untuk meningkatkan produktivitas publikasi karya ilmiah dalam jurnal internasional terindeks. Penelitian ini merupakan penelitian survei yang dilakukan di Program Pascasarjana Universitas Negeri Yogyakarta (PPs UNY) dengan responden berjumlah 74 orang. Teknik pengumpulan data menggunakan angket. Teknik analisis data menggunakan teknik analisis statistik deskriptif. Hasil penelitian dijelaskan sebagai berikut. 1) Faktor penghambat publikasi karya ilmiah pada jurnal internasional terindeks bersumber dari faktor eksternal yaitu kesibukan kerja, besarnya biaya, terbatasnya langganan jurnal cetak, terbatasnya langganan jurnal online, dan terbatasnya akses jurnal cetak. 2) Harapan Mahasiswa PPs UNY untuk meningkatkan produktivitas publikasi karya ilmiah dalam jurnal internasional terindeks yaitu perbaikan dan peningkatan dalam sosialisasi, akses informasi dan layanan, pelatihan penulisan dan bahasa Inggris, bantuan alih bahasa secara gratis, menjalin kerjasama dengan berbagai pihak, serta langganan jurnal online dan cetak